Keragaman Genetik Rusa Sambar (Rusa unicolor), Pemanfaatan dan Implikasinya Untuk Konservasi - Wirdateti, Wirdateti (Perhimpunan Biologi Indonesia, 2012)
Genetic Diversity of Sambar Deer (Rusa unicolor) in Utilization and Implications forÂ Conservation. The deer sambar (Rusa unicolor) is one of species of Genus Rusa, was widelyÂ distributed in South Asia antil South East Asia. This species in Indonesia was widely distributedÂ in Kalimantan and Sumatra island, but now, the hunting, poaching and habitat loss haveÂ reduced its populations drasstically. In order to provide useful information for its conservations.Â The genetic diversity and population structure of the wild sambar deer was observed byÂ analyzing the 962 bp long of fragment mitochondrial DNA (mtDNA) control region (D-loop)fragment. The result detected, twenty different haplotypes from 22 samples from Borneo andÂ Sumatra. Overall, sambar deer have a relatively high genetic diversity compared to other theÂ ceervid species, with a haplotype diversity (h) 0.9870 and nucleotide diversity (Ã°) 2.931Â±0.260%.The genetic distance of Borneo populations (East Borneo) higher compared with SumatraâsÂ populations that is d = 0.018Â±0.003 on Borneo and d = 0.009Â±0.002 on Sumatra. The structureÂ of phylogenetic tree showed that two populations were separate based on the haplotypesÂ differences.Keywords: conservation, control region, genetic diversity, sambar deer.